1998
DOI: 10.1007/bf02507158
|View full text |Cite
|
Sign up to set email alerts
|

Various aspects of inhibition of photosynthesis under light/chilling stress: “Photoinhibition at chilling temperatures” versus “chilling damage in the light”

Abstract: At chilling temperatures, plants suffer damage to photosynthesi~ The sites and the mechanisms involved in this damage differ under different chilling conditions, The current status of our understanding of this damage is reviewed, and how chilling temperatures affect photosynthesis is discussed with emphasis on the role of light and the phase separation of membrane lipids,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 54 publications
7
54
1
2
Order By: Relevance
“…This agrees with the results of other experiments made on cold-stressed plants, where the increased efficiency of electron transport around PS1 complex was observed (Sonoike 1998, Pessarakli 1999. PS1 is probably less susceptible to low temperature-induced damage compared to PS2, particularly under low-light conditions when no photodamage to this complex should occur (Nie and Baker 1991, Körnerová and Holá 1999, Sonoike 1998, Pessarakli 1999. All three biotypes examined responded to the cultivation at 10°C by an increase of the PS1 activity; this increase was slightly higher in the atrazine-sensitive biotypes Jihlava and Karlín than in the resistant biotype Bubny (Figure 4).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This agrees with the results of other experiments made on cold-stressed plants, where the increased efficiency of electron transport around PS1 complex was observed (Sonoike 1998, Pessarakli 1999. PS1 is probably less susceptible to low temperature-induced damage compared to PS2, particularly under low-light conditions when no photodamage to this complex should occur (Nie and Baker 1991, Körnerová and Holá 1999, Sonoike 1998, Pessarakli 1999. All three biotypes examined responded to the cultivation at 10°C by an increase of the PS1 activity; this increase was slightly higher in the atrazine-sensitive biotypes Jihlava and Karlín than in the resistant biotype Bubny (Figure 4).…”
Section: Resultssupporting
confidence: 93%
“…However, this can hardly be the case in our experiments where measurements of PS1 activity were done on isolated chloroplasts supplied with sufficient amount of artificial electron acceptors and donors. On the other hand, the decrease in the ratio of reduced/oxidized form of plastoquinone, which should result from the lowered efficiency of the PS2 photosynthetic electron transport, could lead to the changes in the redox state of chloroplasts, and such changes are known to have far-reaching consequences on the quantity and function of various components of photosynthetic apparatus including PS1 (Wise 1995, Sonoike 1998. The comparison of HRA and PS1 activity in the ALS inhibitors-resistant, atrazine-sensitive Jihlava biotype with the Karlín biotype (sensitive to both types of herbicides) showed that the values of both parameters measured for the Jihlava biotype were lower than those measured for the Karlín biotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4°C to 6°C) may not substantially disrupt photosynthetic metabolism, but could cause damage to the photosynthetic apparatus. High light intensity during chilling could cause more severe chilling damage when compared to little or no light during the chilling (Sonoike, 1998). This may also provide a partial explanation for the observed relationship between chilling damage level and plant reaction (i.e., photosynthetic metabolism) after chilling challenge.…”
Section: Discussionmentioning
confidence: 99%
“…No caso da cultura da soja, elevadas temperaturas do ar durante o crescimento reduzem o tempo para o florescimento (Major et al, 1975). Em condições tropicais e subtropicais, baixas temperaturas limitam severamente o crescimento das plantas, cuja capacidade fotossintética é reduzida em razão do decréscimo da eficiência quântica no fotossistema II e atividades do fotossistema I, e ocorre também redução dos ciclos para a formação de enzimas e ATP, no estroma das plantas C3 (Sonoike, 1998;Allen & Ort, 2001).…”
Section: Introductionunclassified